Vertical equilibrium simulation for industrial-scale CO2 storage in heterogeneous aquifers - Hatem Alamara; Christophe Blondeau; Sylvain Thibeau; Igor Bogdanov (Scientific Reports)
Abstract Vertical equilibrium (VE) simulation has re-emerged recently as an efficient approach for simulating geological CO2 storage in aquifers. The approach is well-established and traditionally applied for simulating storage in homogeneous formations. In this study, we assess its application to large-scale heterogeneous aquifers. We focus on sharp-interface models due to their utility during the screening phase of storage aquifer assessment. The study demonstrates that neglecting geological heterogeneity in the vertically-averaged relative permeability and pseudo-capillary pressure may lead to significant errors in predicted CO2 plume extents. These errors result from unjustifiably assuming homogeneous-acting formations to highly heterogeneous formations. Their magnitudes depend on the heterogeneity level and the simulation timescale. We leverage existing simulators to run VE models and discuss their shortcomings. Our investigation highlights VE simulation as a promising tool for dedicated future development in the industry, particularly through automation of the proposed screening workflows for probabilistic prediction of CO2 plume migration. We also propose treating VE models as metamodels (models of vertically-discretized models with infinite vertical resolution), particularly in contexts where geological data are limited. The study concludes with reporting a successful implementation of a sharp-interface VE simulation in a real, heterogeneous formation. While our conclusions are drawn specifically for geological CO2 storage, they are applicable to other fluids in similar settings.